Avian Chemical Signatures: An Overview - Alves Soares, Tatjana; Barbara, A. Caspers; Loos, Helene (Chemical Signals in Vertebrates 15, 2023)
Intraspecific communication in birds can involve the visual, auditory, tactile, and olfactory senses. Although the latter is one of the least studied signalling modalities in birds, research of the last decades showed that a bird’s chemical profile varies according to different parameters. Here, we summarise current knowledge about chemical signatures of the volatile as well as the non-volatile fraction of preen oil, feathers and a bird’s overall odour, considering the potential transfer of information regarding species, genetic distance/compatibility, individual identity, sex, breeding season, and age. We found good agreement between the results of the publications reviewed here with regard to the substance classes being involved in the related chemical signatures. However, conclusive findings of specific compounds or mixtures of compounds as key constituents of the considered chemical signatures are rare. Moreover, none of the investigated parameters was characterised by only one compound, supporting the notion that they are encoded in chemical signatures being built of multiple compounds. Based on the overview of available insights into avian chemical signatures, we finally delineate lines of future research in this emerging field of research.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Age signature; Bird odour; Breeding season signature; Genetic signature; Individual identity signature; Infochemicals; Olfaction; Sex signature; Species signature; Volatilome